Perbandingan pencapaian hasil belajar siswa antara penerapan bahan ajar fisika terintegrasi kecerdasan sosial dan bahan ajar di sekolah pada materi gerak parabola dan gerak melingkar pada siswa kelas X SMAN 16 Padang - yenni nofita sari; Zulhendri Kamus (Universitas Negeri Padang, 2019)
The application of the 2013 curriculum in each education unit aims to enable students to increase knowledge, build character values and noble character in themselves in order to behave well in daily life. This means that there is continuity between attitudes, knowledge and skills that cannot be separated. The reality in the field of student competency achievement is still low and dominated by knowledge and skills competencies without involving attitude competency as a result of the participant. This study aims to determine the differences in student learning outcomes using integrated social intelligence teaching materials and the teaching materials which are available in schools at SMAN 16 Padang. The type of research conducted is quasi-experimental research with a randomized posttest only control group design. The population in this study were all of class X students of SMAN 16 Padang who were enrolled in the 2018/2019 Academic Year. Sampling in the study was conducted by combining purposive sampling technique and cluster random sampling. The sample in this study was class X MIA 1 as the experimental class 1, and class X MIA 3 as the experimental class 2 which numbered 72 students. The data in this study were analyzed using analysis of score to value conversion, descriptive statistics, normality test, homogeneity test and two similarity test averages at the 0.05 significance level for all student competencies. The results of the study concluded that there were significant differences in student physics learning outcomes from the aspects of social attitudescompetency, knowledge, and skills of students between students using Social Intelligence Integrated Physics Teaching Materials and the students who did not use Physics Integrated Social Intelligence Teaching Materials. It is proven from the data analysis of all competencies. After getting the analysis of social attitudes competency data, knowledge and the skills normally distributed data and homogeneous, then through the two similarity tests on average, the social attitudes competency is obtained tcount = 3.789, in the knowledgecompetencythe tcount = 3.544, and in the skillscompetencyt count = 2.538 , while the ttable value (0.975; 70) = 1.9966 which proves that the tcount is greater than t table, with Ho acceptance criteria if or -1.996 <th<1.996 then it can be concluded that Ho is rejected and Hi is accepted, and it means there are significant differences in learning outcomes between the application of integrated social intelligence teaching materials with teaching materials at school.